Effect of transgenerational diabetes via maternal lineage in female rats - Quintanilha Gallego, Franciane [UNESP]; Barco, Vinícius Soares [UNESP]; Sinzato, Yuri Karen [UNESP]; Paula, Verônyca Gonçalves [UNESP]; de Souza, Maysa Rocha [UNESP]; Lopes da Cruz, Larissa [UNESP]; Roy, Sayon; Corrente, José Eduardo [UNESP]; Damasceno, Débora Cristina [UNESP] (Elsevier, 2024)
Aim: To investigate the transgenerational effect of maternal hyperglycemia on oxidative stress markers, lipid profile, glycemia, pancreatic beta (β)-cells, and reproductive outcomes in the F2 adult generation. Additionally, to expand the knowledge on transgenerational diabetes the F3 generation at birth will be evaluated. Methods: On day 5 of postnatal life female Sprague-Dawley rat newborns (F0 generation) were distributed into two groups: Diabetic (Streptozotocin-STZ, 70 mg/kg body weight, subcutaneous route) and Control rats. Adult female rats from the F0 generation and subsequently the F1 generation were mated to obtain the F2 generation, which was distributed into F2 generation (granddaughters) from control (F2_C) and diabetic (F2_D) rats. Oral Glucose Tolerance Test (OGTT), the area under the curve (AUC), blood biochemical analyses, and pancreatic morphology were analyzed before pregnancy. Reproductive outcomes were performed at the end of pregnancy. At birth, the glycemia and body weight of F3_C and F3_D rats were determined. p < 0.05 was considered significant. Results: F2_D had higher body weight, triglyceride levels, and percentage of insulin-immunostained cells, contributing to glucose intolerance, and insulin resistance before pregnancy. At day 21 of pregnancy, the F2_D showed increased embryonic losses before and after implantation (84.33 and 83.74 %, respectively). At birth, F3_D presented hyperglycemia, and 16.3 % of newborns were large for pregnancy age (LGA). Conclusion: Diabetes induction since the neonatal period in the first generation (F0) led to transgenerational (F2 and F3 generations) changes via the maternal lineage of female rats, confirming the relevance of control strictly the glycemia all the time.
Keywords: Diabetogenic tendency; Hyperglycemia; Macrosomia; Pregnancy; Rodents